1980
DOI: 10.1073/pnas.77.8.4979
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of cytoskeletal components on the surface of leukemia cells and of lymphocytes transformed by mitogens and Epstein-Barr virus.

Abstract: Lactoperoxidase iodination and two-dimensional electrophoresis of the labeled proteins have demonstrated well-characterized cytoskeletal proteins (actin and tubulins) on the surface of human lymphocytes undergoing blastogenic transformation and of certain malignant human cells. Such proteins could not be detected on the surface of normal resting human lymphocytes. The most prominent cytoskeletal rotein identified on the surface membrane of mitogen-transformed T and B lymphocytes was actin. In Epstein-Barr viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…As an independent approach, we demonstrated the presence of actin on the catecholaminergic cell surface using FACS analyses. Several reports suggest the presence of a cell-surface form of actin on other cell types (Owen et al, 1978;Bachvaroff et al, 1980;Sanders and Craig, 1983;Moroianu et al, 1993;Dudani and Ganz, 1996;Andronicos and Ranson, 2001;Dudani et al, 2005). Actin mediates autoproteolysis of plasminogen to angiostatin on cancer cells (H. Wang et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…As an independent approach, we demonstrated the presence of actin on the catecholaminergic cell surface using FACS analyses. Several reports suggest the presence of a cell-surface form of actin on other cell types (Owen et al, 1978;Bachvaroff et al, 1980;Sanders and Craig, 1983;Moroianu et al, 1993;Dudani and Ganz, 1996;Andronicos and Ranson, 2001;Dudani et al, 2005). Actin mediates autoproteolysis of plasminogen to angiostatin on cancer cells (H. Wang et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, surface-associated actin could be displaced by heparin or angiogenin (Moroianu et al, 1993). Controls indicated that lymphocytes did not bind actin added exogenously, either in purified form or when incubated in cellconditioned medium (Bachvaroff et al, 1980;Sanders and Craig, 1983). Although actin is present in fetal calf serum, the form of actin on endothelial cells is smooth muscle a-actin, not the same type as found in fetal calf serum (Moroianu et al, 1993).…”
Section: Actin and Other Cytoskeletal Proteinsmentioning
confidence: 99%
“…At least eight research groups have reported the existence of actin at the external face of the cell surface in lymphocytes (Owen et al, 1978;Bachvaroff et al, 1980;Rubin et al, 1982;Sanders and Craig, 1983), monocytes (Por et al, 1991), endothelial cells (Pardridge et al, 1989;Moroianu et al, 1993), and L cells (Rosenblatt et al, 1985). (Evidence and control experiments will be discussed only for this first example, but may be taken as representative of the other proteins and locations mentioned below.)…”
Section: Actin and Other Cytoskeletal Proteinsmentioning
confidence: 99%
See 2 more Smart Citations